The National Income from "Forestry And Logging" Sector - Satyamurthi, K. R. (Indian Forester, 1977)
The main aim of this article is to acquaint tbe foreater to the concept of 'National Income' from Forestry and Logging Sector. The present method of computing has been described. The way in wbich the expenditure on new plantationa has to be treated is critically examined.